Treatment delay and tumor size in patients with oral cancer during the first year of the COVID-19 pandemic - Semmelmayer, Karl; Mrosek, Jan Bernd; Zittel, Sven; Pilz, Maximilian; Held, Thomas; Adeberg, Sebastian; Ristow, Oliver; Hoffmann, Jürgen; Engel, Michael; Freudlsperger, Christian; Moratin, Julius (Head & neck, 2021)
Background We set out to investigate how the ongoing coronavirus pandemic affected the size of tumors and the duration of treatment delay in patients with surgically treated oral squamous cell carcinoma. Methods Patients with surgically treated oral cavity squamous cell carcinoma were assessed retrospectively and divided into two groups depending on when they had first presented at our clinic. Patients presenting from 2010 to 2019, that is, before COVID-19 onset (n = 566) were compared to patients presenting in 2020 (n = 58). Results A total of 624 patients were included. Treatment delay was significantly longer in 2020 (median = 45 days) versus 2010-2019 (median = 35 days) (p = 0.004). We observed a higher pathological T classification in 2020 (p = 0.046), whereas pathological N classification was unchanged between groups (p = 0.843). Conclusions While extraordinary efforts continue to be made in the context of the pandemic, it is imperative that this does not lead to significant disadvantages for many people with oral cancer.